Analisis Pola Komunikasi Diskominfo Jawa Barat di Media Sosial: Kajian Sintaksis, Wacana, dan Keterlibatan Publik - Fikri Hakim; Yuni Ertinawati; Aveny Septi Astriani (Publikasi Indonesia, 2025)
This study aims to analyze the communication patterns used by the West Java Diskominfo in social media, focusing on syntactic aspects, discourse strategies, and the effectiveness of digital communication. The method used in this study is a qualitative method with critical discourse analysis techniques. There are several approaches in the analysis process, ranging from a syntactic approach to identify the structure of active and passive sentences; discourse analysis approaches to examine messaging strategies, cohesion, and coherence; and analysis of audience engagement in digital communications. The data used is in the form of discourse and content that is under the responsibility of the West Java Provincial Communication and Information Department. The source of data for this study refers to the official web and social media accounts managed by the West Java Provincial Diskominfo. The results of the study show that the West Java Diskominfo uses more active sentences in its social media uploads, which gives a more direct and firm impression. In discourse strategies, the narrative patterns and arguments used tend to clarify the problem before offering solutions that the government does. In addition, the use of persuasive words and hashtags strengthens the consistency and branding of local government communication. In terms of digital communication, audience engagement is higher in uploads that discuss public policy and strategic issues. The effectiveness of messages is enhanced through the use of multimedia and language styles tailored to audience segments. This study concludes that the communication pattern of the West Java Diskominfo is quite effective, but it can still be optimized by increasing two-way interaction and the use of interactive visual elements.